A feasibility study of a manualized resilience-based telehealth program for persons with multiple sclerosis and their support partners. Issue 3 (August 2020) - Halstead, Elizabeth J; Leavitt, Victoria M; Fiore, Damian; Mueser, Kim T
Background: Resilience is a protective factor that emerges when individuals are faced with challenges and stressors. Multiple sclerosis (MS) is a chronic neurological disease that introduces a great deal of stress for the individual and his/her support partner. We designed a telehealth resilience-building dyadic program for persons with MS (PwMS) and their support partners. Objectives: To evaluate the feasibility of the resilience intervention. The secondary objective was to assess the benefits of the intervention. Methods: Sixty-two participants ( M  = 49.5 years, 31 dyads of PwMS) and support partners) were recruited to participate. Out of the 31 dyads, 26 were spouses, 2 were cohabiting partners, and 3 were parent–child dyads. Results: The feasibility goals of the intervention were met, as determined by high participant satisfaction and acceptable completion rates. Preliminary outcomes relating to resilience were positive, suggesting that this intervention had a positive impact on participants. Conclusions: To the best of our knowledge, this is the first resilience-building intervention delivered via telehealth for both PwMS and their support partners. The study showed an increase in resilience-building skills for addressing the challenges faced by PwMS and their support partners. These skills can be promoted and taught, clinically supported by telehealth, an affordable, accessible healthcare solution. Trial Registration at ClinicalTrials.gov (NCT03555253).